2013
DOI: 10.1186/1756-0500-6-146
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma encephalitis in HIV/AIDS patients admitted to the Douala general hospital between 2004 and 2009: a cross sectional study

Abstract: BackgroundIt is estimated that about a third of the world’s population is chronically infected with Toxoplasma gondii. Toxoplasma encephalitis (TE), which occurs as a reactivation of quiescent chronic infection, is one of the leading causes of central nervous system (CNS) infection in AIDS. Its diagnosis in most centres still remains difficult. We opted to describe the clinical and radiological features of TE as well as in-hospital outcome and its associated factors.MethodsWe carried out a cross sectional stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 18 publications
1
29
0
1
Order By: Relevance
“…4 In a study involving 97 HIV patients with toxoplasma encephalitis, the median CD4 count was 68 cells/µl. 5 Similar findings have been observed in studies from Puerto Rico and Brazil where toxoplasma encephalitis was observed in patients with low CD4 count. 6,7 The incidence of toxoplasmosis varies by country and depends on the prevalence of T. gondii infection in the general population.…”
Section: Discussionsupporting
confidence: 76%
“…4 In a study involving 97 HIV patients with toxoplasma encephalitis, the median CD4 count was 68 cells/µl. 5 Similar findings have been observed in studies from Puerto Rico and Brazil where toxoplasma encephalitis was observed in patients with low CD4 count. 6,7 The incidence of toxoplasmosis varies by country and depends on the prevalence of T. gondii infection in the general population.…”
Section: Discussionsupporting
confidence: 76%
“…Penelitian oleh Goita et al (2012) juga ditemukan hal yang sama yaitu kejang merupakan gejala yang umum ditemukan pada toksoplasmosis cerebri. 14,15 Dari hasil CT scan didapatkan gambaran lesi hipodens multiple dengan kesan suatu abses serebri. Pada pasien HIV, gambaran toksoplasmosis serebri sering muncul dalam bentuk abses serebri.…”
Section: Laporan Kasusunclassified
“…In Cameroon, some evidence have been reported on HIV/toxoplasmosis co-infection [14][15][16][17]. Of note, these previous reports showed emphasis on mortaility trensds [14], IgG and IgM testing [15], toxoplasmosis in hospitalised patients [16], and neurological disturbances associated with HIV/AIDS [17]. However, data on anti-toxoplasma gondii quantification, as well as its possible correlation with standard biomarkers of HIV infection (viral load and CD4), have not yet been ascertained.…”
Section: Introductionmentioning
confidence: 99%